Understanding the Biomechanical Factors Related to Successful Balance Recovery and Falls: A Literature Review - Junwoo Park; Jongwon Choi; Woochol Joseph Choi (Korean Research Society of Physical Therapy, 2023)
Background: Despite fall prevention strategies suggested by researchers, falls are still a major health concern in older adults. Understanding factors that differentiate successful versus unsuccessful balance recovery may help improve the prevention strategies. Objects: The purpose of this review was to identify biomechanical factors that differentiate successful versus unsuccessful balance recovery in the event of a fall. Methods: The literature was searched through Google Scholar and PubMed. The following keywords were used: 'falls,' 'protective response,' 'protective strategy,' 'automated postural response,' 'slips,' 'trips,' 'stepping strategy,' 'muscle activity,' 'balance recovery,' 'successful balance recovery,' and 'failed balance recovery.' Results: A total of 64 articles were found and reviewed. Most of studies included in this review suggested that kinematics during a fall was important to recover balance successfully. To be successful, appropriate movements were required, which governed by several things depending on the direction and characteristics of the fall. Studies also suggested that lower limb muscle activity and joint moments were important for successful balance recovery. Other factors associated with successful balance recovery included fall direction, age, appropriate protective strategy, overall health, comorbidity, gait speed, sex and anticipation of the fall. Conclusion: This review discusses biomechanical factors related to successful versus unsuccessful balance recovery to help understand falls. Our review should help guide future research, or improve prevention strategies in the area of fall and injuries in older adults.